Whole-Exome Sequencing Reveals CLCNKB Mutations in a Case of Sudden Unexpected Infant Death. (July 2015) - Lopez, Hector U.; Haverfield, Eden; Chung, Wendy K.
Cases of sudden unexpected infant death (SUID) leave many families devastated, especially in those without an identified cause of death. Here, we describe the case of an apparently healthy 15-day-old infant who died suddenly and unexpectedly. Through whole-exome sequencing, the infant was posthumously found to have 2 mutations in the CLCNKB gene, leading to a molecular diagnosis of Bartter syndrome type III, the likely cause of death. This case illustrates the potential utility of exome sequencing in cases of SUID to suggest a diagnosis, with important implications for families, allowing them to come to closure over the cause of death, informing their future reproductive decisions, and minimizing the risk of recurrence.